Improved results demonstrated in the 2017 national audit of early syphilis management in the United Kingdom. (March 2020) - Menon-Johansson, AS; Curtis, H; Mohammad, H; Hamlyn, E; Hughes, A; McClean, H; Pal, N; Tayal, S; Sullivan, AK
The revised British Association of Sexual Health and HIV UK guidelines on the management of syphilis were published in 2015 and this audit measures performance against those standards and recommendations. Although not included in the guideline recommendations, an exploratory question on clinics' HIV testing policy was also included. The audit was conducted over a two-month period in 2017 in genitourinary medicine (GUM) clinics across the UK of cases presenting in 2016. A total of 161 GUM clinics participated, and data were collected for 3017 cases. The standard for adherence to recommended treatment was met (97%, standard: 97%) and almost met for documented pre-treatment syphilis serology (95%, standard: 97%). Even though only 74% of patients had a documented action in relation to informing sexual contacts (standard: 97%), the standard for contacts seen and tested per index case within four weeks was met (0.9, standard: 0.6). Finally, those clinics with a formal policy on HIV testing after a syphilis diagnosis were twice as likely to test after the HIV window period, compared to clinics without a policy; a concurrent HIV diagnosis was made in 75 (3%) patients. More work is required to standardize documented delivery of effective partner notification and a formal policy on HIV testing appears to be effective.